Tongue trail to kidney - Krunal Harishchandra Khobragade; Ganesh K. Bakshi; Gagan Prakash; Santosh Menon (Indian Journal of Medical and Paediatric Oncology)
Renal cell carcinoma (RCC) has the propensity to metastasize to any organ in the body. Tongue metastases from RCC is very rare with most of them being metachronous in nature. We present a rare case where patient presented with a tongue lesion leading to a diagnosis of RCC. Surgery is the preferred modality of treatment for tongue metastases.